2022
DOI: 10.1155/2022/7476477
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship and Changes of Liver Blood Supply, Portal Pressure Gradient, and Liver Volume following TIPS in Cirrhosis

Abstract: Aim. Transjugular intrahepatic portosystemic shunt (TIPS) alters the liver blood supply and reduces portal pressure. This study was to investigate the changes and associations of the hepatic blood flow, liver volume, and portal pressure gradient (PPG) after TIPS in liver cirrhosis. Methods. Twenty-one patients with liver cirrhosis who received TIPS were recruited. The contrast CT images were used to assess the iodine density (ID) of liver parenchymal and liver volume. The ID of the liver parenchyma was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Consistent with our results, a meta-analysis of 859 patients by Chen et al [ 6 ] reported that TIPS placement did not increase the risk of HCC development among patients with cirrhosis. This might be due to the reduced proliferative activity of hepatocytes observed after TIPS placement, as reported by Delhaye et al [ 29 ] In contrast, two different studies investigated the impact of TIPS on hepatic blood flow [ 30 , 31 ] noted increased hepatic blood flow, particularly during the arterial phase of imaging. This observation raises concerns about potential HCC growth subsequent to arterialization of the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our results, a meta-analysis of 859 patients by Chen et al [ 6 ] reported that TIPS placement did not increase the risk of HCC development among patients with cirrhosis. This might be due to the reduced proliferative activity of hepatocytes observed after TIPS placement, as reported by Delhaye et al [ 29 ] In contrast, two different studies investigated the impact of TIPS on hepatic blood flow [ 30 , 31 ] noted increased hepatic blood flow, particularly during the arterial phase of imaging. This observation raises concerns about potential HCC growth subsequent to arterialization of the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Although infusion and albumin treatment is the rst-line treatment for ascites, even if it is effective once, ascites Will still be repeated. Although the use of TIPS for ascites remains controversial and challenging, TIPS does improve patient survival and can control the repeated occurrence of ascites [5][6][7][8] However, ascites recurrence after TIPS is not only associated with postoperative PPG, but also with disease severity (as measured by the Child-Pugh score) and low sodium levels. For patients with cirrhotic ascites, TIPS can better control ascites and improve the 1-year survival of patients with refractory ascites, while the risk of hepatic encephalopathy was not signi cantly increased [9] .…”
Section: Discussionmentioning
confidence: 99%